Evaluation of blood-brain barrier function by quotient alpha2 macroglobulin and its relationship with interleukin-6 and complement component 3 levels in neuropsychiatric systemic lupus erythematosus. - Tomoyuki Asano; Hiromi Ito; Yoshinobu Kariya; Kyoka Hoshi; Akioh Yoshihara; Yoshikazu Ugawa; Hideharu Sekine; Shunsei Hirohata; Yoshiki Yamaguchi; Shuzo Sato; Hiroko Kobayashi; Kiyoshi Migita; et al. (PLoS ONE, 2017)
Although quotient of alpha2 macroglobulin (Qα2MG) was previously reported to be useful for the evaluation of blood-brain barrier (BBB) function, it is not commonly used. We therefore evaluated BBB function among the various subsets of neuropsychiatric systemic lupus erythematosus (NPSLE) using quotient Q α2MG. Furthermore, we determined the correlation between Q α2MG and cerebrospinal (CSF) interleukin (IL)-6 level and quotient complement component 3 (Q C3). To determine intrathecal production of C3, the C3 index (Q C3/Q α2MG) was also calculated. Fifty-six patients with SLE were included in this study. Of these, 48 were diagnosed with NPSLE, consisting of 30 diffuse NPSLE patients (acute confusional state (ACS): n = 14, non-ACS: n = 16) and 18 patients with focal NPSLE. CSF IL-6 concentration, and paired serum and CSF levels of α2MG and C3, were measured by enzyme-linked immuno solvent assay (ELISA). The Q α2MG, Q C3, and C3 index were then calculated. Q α2MG, Q C3, and IL-6 concentrations in the CSF were significantly elevated in NPSLE compared with non-NPSLE. Among the subsets of NPSLE, significant increases in Q α2MG, CSF IL-6, and Q C3 were observed in ACS compared with non-ACS or focal NPSLE. There was a positive correlation between CSF IL-6 level and Q α2MG, as well as between Q C3 and Q α2MG, in diffuse NPSLE. There were no significant differences in C3 index between NPSLE and non-NPSLE, as well as among the subgroups of NPSLE. Our study suggests that BBB disruption is present in ACS, and elevated levels of IL-6 and C3 in CSF in diffuse NPSLE, especially in ACS, might result from their entry to the CSF from the systemic circulation through the damaged BBB, as well as increased intrathecal production. Furthermore, Q α2MG might be useful for the evaluation of BBB integrity.